Stabilitas Sampel Darah Terhadap Profil Hematologi Dengan Metode Otomatis - puspitasari Puspitasari; Andika Aliviameita (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
Sample stability, part of the pre-analytic phase is an important component that can affect clinical laboratory results. Handling of blood samples and storage methods can significantly affect the results of hematological examinations. This study aims to determine the effect of delay time and storage temperature on the results of the examination of leukocyte count, hemoglobin level, erythrocyte count, hematocrit level, and platelet count. The type of research used is a quantitative analysis using laboratory experimental methods. The research was carried out in the hematology laboratory of the Medical Laboratory Technology Study Program, University Muhammadiyah of Sidoarjo in September - December 2021. The results of the Two Way ANOVA test showed that there was no statistically significant effect between the length of time delay and storage temperature on the results of the examination of leukocyte count, hemoglobin level, number of erythrocytes. Friedman test results showed that there was a statistically significant effect between the length of time of delay and storage temperature on hematocrit levels and platelet counts.